Balloon catheter vs oxytocin alone for induction of labor in women with a previous cesarean section: A randomized controlled trial. (6th September 2019) - Sarreau, Mélie; Isly, Helene; Poulain, Patrice; Fontaine, Brigitte; Morel, Olivier; Villemonteix, Pascal; Mares, Pierre; Mousty, Eve; Godard, Alain; Ragot, Stephanie; Pierre, Fabrice
Abstract: Introduction: The aim of this study was to compare the efficacy and maternal‐neonatal morbidity between balloon catheter and oxytocin for induction of labor in women with a previous cesarean section and an unfavorable cervix. Material and methods: This open‐label randomized controlled trial took place in seven French hospitals. Inclusion criteria were medical indication for labor induction in pregnant women, ≥37 weeks, with lower segment cesarean section, Bishop score ≤4, no pre‐labor rupture of membranes, singleton fetus in cephalic presentation. Women were allocated randomly to induction with a 50‐mL balloon catheter for 12 hours or a low‐dose oxytocin infusion. Primary outcome was the rate of vaginal birth. Secondary outcomes were maternal and neonatal complications. Results: The study enrolled 204 women from 26 December 2010 to 31 December 2013: 101 were allocated to receive balloon catheter and 103 to oxytocin. Vaginal birth rate was 50% (n = 51) in the balloon catheter group vs 37% (n = 38) in the oxytocin group ( P = 0.050). Maternal and neonatal morbidity did not differ between balloon catheter and oxytocin groups: two uterine dehiscences vs one, one vs four maternal infections, five vs two hemorrhages and 11 vs five neonatal transfers, respectively. Heterogeneity of treatment effect for vaginal delivery was observed across initial Bishop scores. Balloon catheter was more effective for low values of bishop score. Conclusions: Balloon catheter tended to be associated with a higher probability of vaginal delivery as compared with low‐dose intravenous oxytocin when used for induction of labor in women with a previous cesarean section and low Bishop score at induction.